The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcb.27177
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: EBF1 gene promotes the proliferation and inhibits the apoptosis of bone marrow CD34+ cells in patients with myelodysplastic syndrome through negative regulation of mitogen‐activated protein kinase axis

Abstract: The transcription factor, early B cell factor 1 (EBF1), plays a vital role in the lineage specification involving early B cell development and the onset of myelodysplastic syndrome (MDS). Therefore, to investigate whether or not EBF1 affects MDS as well as the transcription factor's underlying mechanism, we used CD34+ hematopoietic stem cells in bone marrow from patients with MDS. The extracted cells were then transfected with a series of EBF1, short hairpin RNA against EBF1 (shEBF1), and SB203580 (a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Also, the expression of NFATC1 and STAT1 are associated with PD-L1 in bladder urothelial carcinoma [19]. Among other transcription factors, EBF1 has been reported in a variety of tumors and immune-related diseases [20][21][22]. DNA sequencing and qRT-PCR of urine specimens confirmed that EBF1 was different between bladder urothelial carcinoma and normal tissues [23], but this difference did not exist in upper urinary tract tumors [24], suggesting that EBF1 may be bladder-specific.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the expression of NFATC1 and STAT1 are associated with PD-L1 in bladder urothelial carcinoma [19]. Among other transcription factors, EBF1 has been reported in a variety of tumors and immune-related diseases [20][21][22]. DNA sequencing and qRT-PCR of urine specimens confirmed that EBF1 was different between bladder urothelial carcinoma and normal tissues [23], but this difference did not exist in upper urinary tract tumors [24], suggesting that EBF1 may be bladder-specific.…”
Section: Discussionmentioning
confidence: 94%
“…MAPK signaling pathway, ECM receptor interaction was found tightly associated with EBFs determined risk in GC patients. Hou et al[56] found that the EBF1 gene suppresses the activation of MAPK pathway, and promotes the cell proliferation and migration of bone marrow CD34+ cells, but inhibit the cell apoptosis. Interestingly, Kong et al[57] also demonstrated that the p38 MAPK pathway could activate MEF2C to drive B cell differentiation, MEF2C is a co-regulator of EBF1 to impact B cell specific transcription.ConclusionDownloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20210055/914564/bsr-2021-0055.pdf by guest on 14 June 2021…”
mentioning
confidence: 99%